2008
DOI: 10.1152/jn.01251.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic Preconditioning of Presynaptic Calcium Regulation inDrosophila

Abstract: Klose MK, Atwood HL, Robertson RM. Hyperthermic preconditioning of presynaptic calcium regulation in Drosophila. J Neurophysiol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 52 publications
2
34
0
1
Order By: Relevance
“…In addition to the N-type calcium channel, Hsp70s interact with the cytosolic loop of Ca V 2.3 R-type voltage-gated calcium channel [89]. The interaction may be important in decreasing the intracellular calcium overload that accompanies hyperthermic insults [25]. Prior to heat shock or induced elevation, Hsp70 at the D. melanogaster neuromuscular junction stabilizes the intracellular calcium concentration by maintaining near-resting calcium level and promoting calcium clearance in subsequent hyperthermic episodes.…”
Section: Hsp70 In the Stressed Synapsementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the N-type calcium channel, Hsp70s interact with the cytosolic loop of Ca V 2.3 R-type voltage-gated calcium channel [89]. The interaction may be important in decreasing the intracellular calcium overload that accompanies hyperthermic insults [25]. Prior to heat shock or induced elevation, Hsp70 at the D. melanogaster neuromuscular junction stabilizes the intracellular calcium concentration by maintaining near-resting calcium level and promoting calcium clearance in subsequent hyperthermic episodes.…”
Section: Hsp70 In the Stressed Synapsementioning
confidence: 99%
“…Increasing Hsp expression level by overexpression [24], drug induction [21], genetic manipulation [25] and preconditioning [20,[26][27][28] protects the cells/organisms from lethal conditions. The mechanisms underlying the cytoprotective effects of heat shock proteins, specifically the Hsp70s, have been well delineated.…”
Section: Introductionmentioning
confidence: 99%
“…Synaptic failure at the Drosophila neuromuscular junction results from a loss of the ability to regulate intracellular Ca 2ϩ concentrations (Klose et al, 2008). Given these precedents and the time dependence of recovery of the tadpole swim CPG, we believe it to be a reasonable supposition that hyperthermic failure and recovery in this system are closely related to loss and restoration of appropriate ion gradients.…”
Section: Discussionmentioning
confidence: 93%
“…Long-term processes of acclimation (Johnston and Temple, 2002) can modify neuronal properties and change optimal temperature ranges (Behan-Martin et al, 1993). More rapid processes requiring protein synthesis can be activated by heat shock pretreatments (Robertson et al, 1996;Kelty et al, 2002;Armstrong et al, 2006;Rodgers et al, 2007), and in larval Drosophila the stress protein HSP70 has been shown to have a role in protecting locomotion (Xiao et al, 2007), and calcium dynamics at the neuromuscular junction (Klose et al, 2008), from hyperthermia. Recently, the nitric oxide (NO)/ cGMP/protein kinase G pathway has been implicated in rapid adaptation of the temperature sensitivity of motor circuits in insects (Dawson-Scully et al, 2007), but it is not known whether similar mechanisms are operational in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Gangguan regulasi Ca 2+ yang penting untuk presynaps menyebabkan kejadian synaptic plasticity selama beberapa menit sehingga menurunkan aliran impuls synaps. 20 Impuls yang terputus ini menyebabkan ekspresi TNF-α dan SP, biomarker yang terlibat dalam neurogenic switching juga menurun dengan cepat.…”
Section: Analisis Varians (Anova) Pembahasanunclassified